Feature specification, underspecification, and morphophonemic process and feature geometry of Amharic language - Mekt, Gebreiyesu (Yayasan Mitra Persada Nusantara, 2024)
In linguistics, a peculiarity is the most basic unit of phonological structure that can be analysed in phonological theory. Distinguishing traits are categorized according to the natural segment classes they describe: major class traits, larynx traits, manner traits, and place traits. The paper does not have a specific section for methods. However, in this paper the author provides a detailed analysis of the phonological processes of assimilation in the Amharic language. The paper explains how assimilation predominantly takes place contiguously and mainly at word or morpheme boundaries, hence mainly morphophonemic in nature. The author discusses different types of assimilation processes such as voice assimilation, glottalization, palatalization, etc. and provides ample examples from the language. The paper also describes how most of the values in language are predicted on the basis of other features under combinatorial specification and radical under specification. Additionally, the paper describes the patterns of units of phonological analysis in Amharic, which occur in particular regular patterns that need to be discovered for each language. Overall, the paper provides a comprehensive understanding of feature specifications, morphophonemic process, and feature geometry of Amharic language.